The Effect of Drag Flick Drill Training on Shooting Accuracy in Indoor Hockey: (Case Study: Students in Grade X at State Senior High School 14 in Tangerang Regency) - Feisal Farras Assyukur; Nida’ul Hidayah; Widi Kusumah (Journal of Physical Education Health and Sport, 2025)
The purpose of this study was to examine the effect of Drag Flick Drill Training on the shooting accuracy of the boys’ indoor hockey team at State Senior High School 14 in Tangerang Regency. The researcher used an experimental method to prove the effect of a treatment on the outcome of that treatment. This study used a one-group pre-test post-test design. This research design involved measurements through a pre-test administered before the treatment and a post-test conducted after the treatment was given to the sample. The researcher took a population of 27 students and a sample of 13 students. The treatment was given 8 times, twice a week. The sampling technique used in this study was purposive sampling, with the characteristics of the research sample being 13 male students in grade X at State Senior High School 14 Tangerang Regency who had just participated in the indoor hockey extracurricular activity. The instrument used in this test was a Target Game. The results of this study showed a significant effect of Drag Flick Drill Training on the shooting accuracy of male students participating in indoor hockey at State Senior High School 14 Tangerang Regency. Through these drills, students also show greater courage in making decisions to shoot. In addition, students who are able to achieve a high shooting percentage are generally supported by the consistent application of drag flick drills in the training process. It can be concluded that Drag Flick Drill Training has an effect on shooting accuracy.